Analisis Determinan Taksiran Berat Janin pada Ibu Hamil - Putri Utami; Hilda Zulkifli; Hamzah Hasyim (Sarana Ilmu Indonesia (salnesia), 2021)
Low birth weight (LBW) are most likely a cause of increasing the number of infant mortality rate. The incidence of LBW related to many factors such as maternal health, fetal, and environmental factors. Early detection to see fetal growth during pregnancy is to estimated fetal weight. The purpose of this research was to find out the correlation of maternal age, maternal education, maternal occupation, history of parity and nutritional status with estimated fetal weight. The type of research used was analytical observational study with cross sectional approach and collected using questionnaire with total samples of 72 pregnant women. The result of this research showed that there was correlation of maternal age (p=0,04), maternal education (p=0,012), history of parity (p=0,003), nutritional status (p=0,012) with estimated fetal weight. There was no correlation of maternal occupation (p=0,327) with estimated fetal weight. The concludes of this research was pregnant women with non-risky age, higher education, parity 2-3 times and good nutritional status tended to have the weight of the fetus conceived according to gestational age, while maternal occupation would not necessarily affected the estimated fetal weight.